Designer Metal–Organic Frameworks for Size‐Exclusion‐Based Hydrocarbon Separations: Progress and Challenges. Issue 44 (9th July 2020) - Wang, Hao; Liu, Yunling; Li, Jing
Abstract: The separation of hydrocarbons is of primary importance in the petrochemical industry but remains a challenging process. Hydrocarbon separations have traditionally relied predominantly on costly and energy‐intensive heat‐driven procedures such as low‐temperature distillations. Adsorptive separation based on porous solids represents an alternative technology that is potentially more energy efficient for the separation of some hydrocarbons. Great efforts have been made recently not only in the development of adsorbents with optimal separation performance but also toward the subsequent implementation of adsorption‐based separation technology. Emerging as a relatively new class of multifunctional porous materials, metal–organic frameworks (MOFs) hold substantial promise as adsorbents for highly efficient separation of hydrocarbons. This is because of their exceptional and intrinsic porosity tunability, which enables size‐exclusion‐based separations that render the highest possible separation selectivity. In this review, recent advances in the development of MOFs for separation of selected groups of hydrocarbons are reviewed, including methane/C2 hydrocarbons, normal alkanes, alkane isomers, and alkane/alkene/alkyne and C8 alkylaromatics, with a particular focus on separations based on the size‐exclusion mechanism. Insights into tailor‐made structures, material design strategies, and structure–property relationships will be elucidated. In addition, the existing challenges and possible future directions of this important research field will be discussed. Abstract : Metal–organic framework (MOF) materials hold tremendous promise for highly efficient separations of industrially important hydrocarbons owing to their exceptional tunability in pore structure and functionality. Recent progress as well as existing challenges for size‐exclusion‐based hydrocarbon separations with designer MOFs is summarized.